2014
DOI: 10.17722/jorm.v2i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Social Responsibility make any differences when it comes to “Un-substitutable” Product from Customer Point of View

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…SR claims, especially through labels on apparel products, are found to influence consumers' attitudes and purchase intentions (Hyllegard et al, 2012). Literature suggests that consumers do take brands' SR efforts into account for their purchase decisions and their evaluations of such efforts influence the brands' image (Foo and Yazdanifard, 2014). Researchers also found that socially responsible messages influenced the extent to which consumers changed their brand attitudes (Olsen et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SR claims, especially through labels on apparel products, are found to influence consumers' attitudes and purchase intentions (Hyllegard et al, 2012). Literature suggests that consumers do take brands' SR efforts into account for their purchase decisions and their evaluations of such efforts influence the brands' image (Foo and Yazdanifard, 2014). Researchers also found that socially responsible messages influenced the extent to which consumers changed their brand attitudes (Olsen et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers have been found to pay attention to brands' SR efforts for their purchase decisions and their evaluation of the brands' overall image (Foo and Yazdanifard 2014). Consumers were also found to change their brand attitudes based on SR marketing messages from brands (Olsen,Slotegraaf,and 2 G. Bhaduri and J. Ha-Brookshire Chandukala 2014).…”
Section: Literature Review and Research Hypotheses Social Responsibilmentioning
confidence: 99%
“…Others also expounded that the impact of CSR on the buying intentions of consumers is more complicated than he thought where can CSR affect firms directly affect or indirectly, to the purchase intentions, where direct effect is when reflect the activities of corporate social responsibility and consumer or beliefs depending on the degree of consumer confidence that corporate social responsibility and institutional capacity as well as consumer support for the behavior of the social responsibility of companies. Also there is a small segment of the consumers are using the practices of corporate social responsibility and consider them as a criterion for purchase (Mohr & Webb, 2005;Foo & Yazdanifard, 2014;and Xu, 2014).…”
Section: The Relationship Between Csr and Purchase Intentionmentioning
confidence: 99%
“…Through this being formulating hypotheses of the study as follows: Many studies have reached for a direct effect to customer's perception to the dimensions of the practices of corporate social responsibility on the purchase intentions (Mohr & Webb, 2005;Sen et al, 2006;Foo & Yazdanifard, 2014;and Xu, 2014), Also having a direct significant effect between every dimension of corporate social responsibility, which represented in (economic, legal, moral, and philanthropic dimension) on purchase intention (Lantos, 2001;Cornwell & Coote, 2005;Gopal & Srinivasan, 2006;Henderson, 2007;Wang, 2009;Ling et al, 2010;and Deng & Qian, 2011).…”
Section: Models and Hypotheses Of The Study 1) Hypotheses Of The Studymentioning
confidence: 99%
See 1 more Smart Citation